No Difference in Reoperation Rates for Adjacent Segment Disease (Operative Adjacent Segment Disease) in Posterior Cervical Fusions Stopping at C7 Versus T1/T2: A Cohort of 875 Patients—Part 1. Issue 3 (1st February 2022) - Guppy, Kern H.; Royse, Kathryn E.; Fennessy, Jacob; Norheim, Elizabeth P.; Harris, Jessica E.; Brara, Harsimran S.
Abstract : Study Design: A retrospective cohort study with chart review. Objective: To determine whether there is a difference in reoperation rates for adjacent segment disease ([ASD] operative ASD) in posterior cervical fusions (PCFs) that stop at –C7 versus –T1/T2. Summary of Background Data: There are surgical treatment challenges to the anatomical complexities of the cervicothoracic junction. Current posterior cervical spine surgery is based on the belief that ASD occurs if fusions are stopped at C7 although there is varying evidence to support this assumption. Methods: Patients were followed until validated reoperations for ASD, membership termination, death, or March 31, 2020. Descriptive statistics and 5-year crude incidence rates and 95% confidence intervals for operative ASD for PCF ending at –C7 or –T1/T2 were reported. Time-dependent crude and adjusted multivariable Cox-Proportional Hazards models were used to evaluate operative ASD rates with adjustment for covariates or risk change estimates more than 10%. Results: We identified 875 patients with PCFs (beginning at C3 or C4 or C5 or C6) stopping at either –C7 (n = 470) or –T1/T2 (n = 405) with average follow-up time of 4.6 (±3.3) years and average time to operative ASD of 2.7 (±2.8) years. Crude overall incidence rates for stopping at –C7 (2.12% [1.02%–3.86%]) and –T1/T2 (2.48% [1.25%–4.40%]) were comparable with no statistical difference in risk (adjusted hazard ratio = 1.47, 95% confidence interval = 0.61–3.53, P  = 0.39). In addition, we observed no differences in the probability of operative ASD in competing risk time-dependent models (Grey test P   =  0.448). Conclusion: A large cohort of 875 patients with PCFs stopping at –C7 or –T1/T2 with an average follow-up of more than 4 years found no statistical difference in reoperation rates for ASD (operative ASD). Level of Evidence: 3 Abstract : In a large cohort of 875 patients with posterior cervical fusions ranging from C3 to T1/T2 stopping at -C7 or -T1/T2 with an average follow-up of > 4 years found no statistical difference in reoperation rates for ASD (operative ASD).